Assessment of MALDI-TOF MS as Alternative Tool for Streptococcus suis Identification - Pérez-Sancho, Marta; Vela, Ana Isabel; García-Seco, Teresa; Gottschalk, Marcelo; Domínguez, Lucas; Fernández-Garayzábal, José Francisco (Frontiers in Public Health, 2015)
The accuracy of matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) for identifying Streptococcus suis isolates obtained from pigs, wild animals, and humans was evaluated using a PCR-based identification assay as the gold standard. In addition, MALDI-TOF MS was compared with the commercial multi-tests Rapid ID 32 STREP system. From the 129 S. suis isolates included in the study and identified by the molecular method, only 31 isolates (24.03%) had score values ≥2.300 and 79 isolates (61.24%) gave score values between 2.299 and 2.000. After updating the currently available S. suis MALDI Biotyper database with the spectra of three additional clinical isolates of serotypes 2, 7, and 9, most isolates had statistically significant higher score values (mean score: 2.65) than those obtained using the original database (mean score: 2.182). Considering the results of the present study, we suggest using a less restrictive threshold score of ≥2.000 for reliable species identification of S. suis. According to this cut-off value, a total of 125 S. suis isolates (96.9%) were correctly identified using the updated database. These data indicate an excellent performance of MALDI-TOF MS for the identification of S. suis.